The role of the underlying event in the charm-baryon enhancement observed in pp collisions at LHC energies - Zoltán Varga, Anett Misák, Róbert Vértesi (SciPost Physics Proceedings, 2024)
We study the enhanced production of $Λ_c$ charmed baryons relative to that of charmed $D^0$ mesons in proton–proton collisions at LHC energies. We simulated collision events with the enhanced color-reconnection model in PYTHIA 8 MC generator and propose measurements based on the comparative use of different event-activity classifiers to identify the source of the charmed-baryon enhancement. We demonstrate that in this enhanced color-reconnection scenario the excess production is primarily linked to the underlying event and not to the production of high-momentum jets.